Contribution of the Inter-American Institute for Cooperation on Agriculture (IICA) to the Jamaican agricultural sector during 1998. 1998 Annual Report - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The Inter - American Institute for Cooperation on Agriculture (IICA) Office in Jamaica is pleased to present this report, which seeks to keep the agricultural sector informed about our activities and programmes carried out in 1998. The Institute acknowledges the contribution of the private sector, national, regional and international organizations and the farmers of Jamaica in the achievements of the results here reported. Special mention must be made of the cooperation of the Minister of Agriculture, the Honourable Roger Clarke and his staff in the Ministry of Agriculture, for their cooperation and support for the work programmes of the IICA office in Jamaica. The hard work and cooperation of the staff of the IICA office in Jamaica is also acknowledged.